(untitled) (Theatrum historiae, 2017)
The study analyses parts of Bashraybung fun Shabbetai Ẓevi dedicated to Leibele Prossnitz, the best-known Moravian adherent of the Sabbatian movement. This early modern Jewish messianic movement is reflected as heretical in academic and non-academic discourse alike and Bashraybung is the only contemporary source describing Leibele Prossnitz’ religious behaviour in more detail. Such described behaviour is put in general context of the early modern European Jewish society to derive those deeds and thoughts of Leibele Prossnitz which are in the text perceived as “normal” (orthodox) and those which are perceived as “extraordinary” (heterodox, heretical). Further, the study distinguishes the deeds and thoughts of Leibele Prossnitz which are specifically Sabbatian, that means those which are shared neither by other messianic enthusiasts of the time nor by other contemporary Jews, and those which are of his own invention. The study is intended to be a contribution to the present discussion on early modern Jewish orthodoxy and heterodoxy.